Gaya Bahasa dalam Berita Nasional cnnindonesia.com Kolom Peristiwa pada Bulan Desember 2023 dan Rekomendasinya Sebagai Bahan Ajar Kelas VII: Language Style in CNNIndonesia.com National News Event Column (December 2023) and its Recommendations as Teaching Material for Grade VII - Azzahra, Ayu; Sutri, Sutri; Suprihatin, Dewi (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The purpose of this study is to describe the language style contained in the CNNIndonesia.com national news events column in the December 2023 edition. The method used in this research is descriptive qualitative method, in which the data that has been collected is then analyzed and described. The subject of this research is the CNNIndonesia.com national news column events edition December 2023, while the object is the language style contained in the CNNIndonesia.com national news column events edition December 2023. The data collection techniques in this research, namely using documentation techniques, listening techniques, and note-taking techniques. The data analysis used the steps according to Miles and Huberman which consisted of data reduction, data presentation, and conclusion drawing or verification. The results of the research that has been conducted regarding the language style in the CNNIndonesia.com national news column events in December 2023, namely from four groups of language styles according to Tarigan, 32 language styles were found.